Catalytic Activity of a Thermoregulated, Phase-Separable Pd(II)-perfluoroalkylphthalocyanine Complex in an Organic/Fluorous Biphasic System: Hydrogenation of Olefins - ÖZER, METİN (SPRINGER, 2009)
A fluoroalkene-soluble tetrakis[heptadecafluorononyl]-substituted Pd(II)-phthalocyanine complex has been studied for olefin (styrene, 1-octene, trans-2-octene and cyclohexene) hydrogenation with molecular hydrogen in an organic/fluorous biphasic system [n-hexane/perfluoromethyl cyclohexane (PFMCH)]. The palladium complex was found to be an active catalyst for styrene (100% conversion, TON = 634) and 1-octene (92%, TON = 596) at 80 degrees C and 15 bar of H-2 after 6 h of reaction time. The catalyst was recycled in nine consecutive reactions for the hydrogenation of styrene without the loss of activity or metal contamination.
Keywords: Biphasic catalysis; Hydrogenation; Phthalocyanine; Palladium complex; Fluorous solvent; FLUOROUS CATALYSIS; OXIDATION; PHTHALOCYANINE; EPOXIDATION; PORPHYRIN; SOLVENTS; ALKENES; CONDENSATION; CYCLOHEXANE; POLYMERS